Suppressor mutations in Rpf2–Rrs1 or Rpl5 bypass the Cgr1 function for pre-ribosomal 5S RNP-rotation. Issue 1 (December 2018) - Thoms, Matthias; Mitterer, Valentin; Kater, Lukas; Falquet, Laurent; Beckmann, Roland; Kressler, Dieter; Hurt, Ed
Abstract During eukaryotic 60S biogenesis, the 5S RNP requires a large rotational movement to achieve its mature position. Cryo-EM of the Rix1-Rea1 pre-60S particle has revealed the post-rotation stage, in which a gently undulating α-helix corresponding to Cgr1 becomes wedged between Rsa4 and the relocated 5S RNP, but the purpose of this insertion was unknown. Here, we show thatcgr1 deletion in yeast causes a slow-growth phenotype and reversion of the pre-60S particle to the pre-rotation stage. However, spontaneous extragenic suppressors could be isolated, which restore growth and pre-60S biogenesis in the absence of Cgr1. Whole-genome sequencing reveals that the suppressor mutations map in the Rpf2–Rrs1 module and Rpl5, which together stabilize the unrotated stage of the 5S RNP. Thus, mutations in factors stabilizing the pre-rotation stage facilitate 5S RNP relocation upon deletion of Cgr1, but Cgr1 itself could stabilize the post-rotation stage. During biogenesis of the eukaryotic 60S ribosome, a large rotational movement of the 5S RNP is required to achieve its mature position. By analyzing extragenic suppressors of crg1—a key factor required for rotation—the authors provide mechanistic insight into a key step of ribosome biogenesis.